2010
DOI: 10.4296/cwrj3504451
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Recharge Assessment in the Chateauguay River Watershed

Abstract: Abstract:The objective of this study was to evaluate groundwater recharge in the Chateauguay River watershed. The Hydrologic Evaluation of Landfill Performance (HELP) model was used to assess daily values of recharge, evapotranspiration and runoff. The study area was divided into a regular grid, 250 m × 250 m, for a total of 47,616 grid elements. The input parameters included soil physical properties, land use, vegetation and climate data. Calibration of HELP was carried out against runoff and baseflow estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 19 publications
(18 reference statements)
7
45
0
2
Order By: Relevance
“…The differences in water levels for humid and dry conditions are smaller at lower elevations; these areas coincide with major discharge zones at the end of the groundwater flow system. Here, the recharge variations are also much lower (Croteau et al, 2010). In the case of recharge under dry conditions, the water level differences seem to be attenuated at low elevation by the groundwater flux coming from the upgradient zones; this contributes to a further decrease water levels in the recharge zones.…”
Section: Zoning Of Aquifer Sensitivitymentioning
confidence: 85%
See 2 more Smart Citations
“…The differences in water levels for humid and dry conditions are smaller at lower elevations; these areas coincide with major discharge zones at the end of the groundwater flow system. Here, the recharge variations are also much lower (Croteau et al, 2010). In the case of recharge under dry conditions, the water level differences seem to be attenuated at low elevation by the groundwater flux coming from the upgradient zones; this contributes to a further decrease water levels in the recharge zones.…”
Section: Zoning Of Aquifer Sensitivitymentioning
confidence: 85%
“…On the other hand, for humid climate conditions, for which precipitation increased by 32%, the average recharge increased only by 15%. Croteau et al (2010) showed that spatially, the recharge variation in response to long-term variations of climate conditions is dependent on the local vertical stratigraphy and hydrogeological conditions. The zones most affected correspond to areas of highest recharge.…”
Section: Zoning Of Aquifer Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were acquired for natural vegetation, including forest, wetland, shrub land, grassland and agricultural areas. The objective of the fieldwork was to collect data to produce a land cover map of the region required for the estimation of the spatial distribution of recharge to the regional aquifer units (Croteau et al, 2010). In addition to the fieldwork, aerial photographs of the region were assembled and used in the analysis.…”
Section: Field Datamentioning
confidence: 99%
“…Latifovic et al (2010) elaborate on operational mapping methods for producing validated regional maps of land cover from optical satellite images. Croteau et al (2010) describe a procedure of using pedological maps, 3D surficial geology and 1D infiltration model (HELP) to obtain spatial and seasonal variation of the recharge rates. Lavigne et al (2010a) describe the hydraulic properties of the bedrock aquifers and present a numerical simulation of the regional groundwater flow and model calibration, while Lavigne et al (2010b) propose a methodology for estimation of the regional sustainability of the groundwater resources.…”
Section: Preface To the Special Issue On The Hydrogeology Of The Chatmentioning
confidence: 99%